2016
DOI: 10.7314/apjcp.2016.17.3.1037
|View full text |Cite
|
Sign up to set email alerts
|

HOXA9 is Underexpressed in Cervical Cancer Cells and its Restoration Decreases Proliferation, Migration and Expression of Epithelial-to-Mesenchymal Transition Genes

Abstract: HOX transcription factors are evolutionarily conserved in many different species and are involved in important cellular processes such as morphogenesis, differentiation, and proliferation. They have also recently been implicated in carcinogenesis, but their precise role in cancer, especially in cervical cancer (CC), remains unclear. In this work, using microarray assays followed by the quantitative polymerase chain reaction (qPCR), we found that the expression of 25 HOX genes was downregulated in CC derived ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
24
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(25 citation statements)
references
References 47 publications
1
24
0
Order By: Relevance
“…QRT-PCR results revealed that HOXA9 was upregulated in SAS cells, which was inconsistent with some of the previous studies. Ruiz et al found that HOXA9 was under-expressed in cervical cancer cells and its restoration decreased the proliferation, migration and expression of epithelial-to-mesenchymal transition (EMT) genes [51]. Hwang JA et al detected that HOXA9 inhibits lung cancer cells migration and its hypermethylation is closely linked with the recurrence in non-small cell lung cancer [52].…”
Section: Discussionmentioning
confidence: 99%
“…QRT-PCR results revealed that HOXA9 was upregulated in SAS cells, which was inconsistent with some of the previous studies. Ruiz et al found that HOXA9 was under-expressed in cervical cancer cells and its restoration decreased the proliferation, migration and expression of epithelial-to-mesenchymal transition (EMT) genes [51]. Hwang JA et al detected that HOXA9 inhibits lung cancer cells migration and its hypermethylation is closely linked with the recurrence in non-small cell lung cancer [52].…”
Section: Discussionmentioning
confidence: 99%
“…SHI et al suggested that secreted protein acidic and rich in cysteine (SPARC) may be a potential therapeutic option for cervical cancer patients [23]. Liliana Alvarado-Ruiz et al found that normal cervical cancer from women without cervical lesions expression HOXA9 but controlling HOXA9 expression appears to be a necessary step during cervical cancer development [24]. These data suggested the crucial roles of cancer related molecules in cervical cancers.…”
Section: Discussionmentioning
confidence: 99%
“…Accumulating evidences have been identi ed that molecular genes may be responsible for tumor initiation, metastasis and recurrence, which playing important role in the detection and treatment of patients with several different cancer types, including cervical cancer [19][20][21][22]. Li et al suggested that fotillin-1 facilitates cervical cancer cell metastasis through Wnt/β-catenin and NF-κB pathway-regulated EMT and the increased fotillin-1 expression is associated with lymph node metastasis and poor prognosis in early-stage cervical cancer [19].…”
Section: Discussionmentioning
confidence: 99%
“…Li et al suggested that fotillin-1 facilitates cervical cancer cell metastasis through Wnt/β-catenin and NF-κB pathway-regulated EMT and the increased fotillin-1 expression is associated with lymph node metastasis and poor prognosis in early-stage cervical cancer [19]. HOXA9 is found downregulated by Liliana Alvarado-Ruiz et al in cervical cancer and controlling HOXA9 expression appears to be a necessary step during cervical cancer development [20]. Torres-Poveda K et al conducted a case-control study paired by age and found the serum levels of Th2 and Th3 cytokines were higher in cervical cancer cases than the controls, representing a risk allelic load for cervical cancer and can be used as a biomarker of susceptibility to this disease [21].…”
Section: Discussionmentioning
confidence: 99%